2016
DOI: 10.3171/2014.12.jns141851
|View full text |Cite
|
Sign up to set email alerts
|

Acute progression of untreated incidental WHO Grade II glioma to glioblastoma in an asymptomatic patient

Abstract: WHO Grade II glioma (low-grade glioma [LGG]) is increasingly diagnosed as an incidental finding in patients undergoing MRI for many conditions. Recent data have demonstrated that such incidental LGGs are progressive tumors that undergo clinical transformation and ultimately become malignant. Although asymptomatic LGG seems to represent an earlier step in the natural course of a glioma than the symptomatic LGG, it is nonetheless impossible to predict at the individual level when the tumor will become malignant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Recent studies have demonstrated that iLGGs grow at a velocity similar to their symptomatic counterparts. 7,20 Not only do iLGGs grow over time, they may also undergo malignant degeneration even in asymptomatic patients. 8,12 Our results demonstrate that tumor volumes increase by about 20 cm 3 over an average of 28 months, and in 1 extreme case rapid progression with malignant transformation occurred that ultimately led to the patient's demise (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that iLGGs grow at a velocity similar to their symptomatic counterparts. 7,20 Not only do iLGGs grow over time, they may also undergo malignant degeneration even in asymptomatic patients. 8,12 Our results demonstrate that tumor volumes increase by about 20 cm 3 over an average of 28 months, and in 1 extreme case rapid progression with malignant transformation occurred that ultimately led to the patient's demise (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…19 Also, in their most recent case report, Cochereau et al illustrate the fact that there can be acute malignant transformation of iLGGs even when the patient remains symptom free. 7 We set out to review a series of cases of iLGGs treated during a period when the general approach at our institution was "watch-and-wait" to determine the characteristics of these tumors and treatment outcomes.…”
mentioning
confidence: 99%
“…Newly apparent contrast enhancement indicating breakdown of the blood brain barrier represents the classical sign of malignant transformation (MT) of these tumors [ 30 ], but preceding changes in advanced MRI investigations may allow identification of patients at risk up to 12 months earlier [ 31 ]. Simple measurement of growth rate [ 19 , 32 , 33 ] and integration of MR spetroscopy [ 18 , 19 , 34 ] are used routinely in most of the centers as predictors of tumor transformation. Both, proton- and phosphorus spectroscopy, available in numerous centers, have been proven to correlate with Ki67 and IDH1 mutation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with iLGGs represent an extremely rare clinical subgroup of LGGs; the incidence ranging between 0.04 and 0.2% in the general population [11]. The natural history of iLGGs prior to discovery is poorly understood [2,12], and the question of clinical management has become a topic of increasing interest in current literature [1][2][3][13][14][15][16][17][18][19][20][21]. None of the above-mentioned studies presented neuropsychological data about patients with incidental brain tumors.…”
Section: Introductionmentioning
confidence: 99%